PRESENT TENDENCIES IN COMMERCIAL EDUCATION. - Jackson, J. Hugh (The Accounting Review, 1926)
Abstract In the attempt to give the student a training in the fundamental principles of the various commercial subjects, and to develop in him the broader outlook which should result from the educational processes, marked changes have occurred in recent years in the methods of presenting materials in the classroom. In the college and university schools of commerce, for example, there has been a decided tendency during the past few years away from the classroom lecture and toward the use of what is commonly known as case material. A second tendency relating to the technical training of the student is the increase in class or socialized instruction. A matter which is almost or fully as important as that of improving the technical training of the student, relates to the introduction in the classroom of the study of ethical principles in business. Originally the apprentice was promised only a technical training in the field of his prospective endeavor. In schools, however, there is a growing desire to teach the student that it is not merely the making of money that counts, but that success in business comes from rendering a real service to the customers and to the employees of the concern, and even to the public generally.